The failure of persuasive communication among social workers in mentoring street children - Aw, Suranto (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article discusses the failure of persuasive communication performed by social workers in the event of mentoring street children in an Indonesian city of Yogyakarta. The existence of the street children in the city remains to be an unweavering issue despite the presence of social welfare provided by governmental agencies and non-governmental organisations (NGOs). A number of shelters takes place to house, mentor and educate these underprivileged kids but has little to no effect in stopping the kids from returning to living on the streets. Failure in communication during the mentoring process between social workers and the kids seems to be one of the determinants of the shorthcomings. Hence, this particular study sought to evaluate the factors that produce such failures. Using a qualitative approach, this study interviewed some social workers in Rumah Singgah Anak Mandiri, one of the famous shelters for street children in Yogyakarta. The results show that the social workers’ lack of persuasive communication skills becomes the main cause of the shortcomings. Precisely, most of them do not possess the capacity, powerful communication, control of emotion, message appeals, organization of the messages, and cultural knowledge in serving counselling sessions with the underprivileged kids.